Pemberdayaan Guru Sekolah Dasar melalui Pelatihan Pembuatan Media Pembelajaran Animasi dengan Powtoon - Dwi Ratnawati; Oktavia Hardiyantari; Vivianti; Tri Widodo; Soraya Fatmawati (Universitas Teknologi Yogyakarta, 2025)
The development of digital technology drives innovation in education, including in delivering more interactive learning materials. However, the use of technology in learning at the elementary school level is still limited, as in SD Gambiranom, Sleman. This study aims to improve teachers' skills in creating animation-based learning media using Powtoon through a training program. The methods used include observation, interactive workshops, mentoring, and evaluation. The evaluation results showed that 85% of participants considered the training materials clear and easy to understand, 78% felt more confident in creating animated media, and 88% considered this training useful for learning. The main obstacles faced include access to devices and the internet, limited time, and adaptation to technology. To overcome these challenges, further training, infrastructure improvements, and learning communities between teachers are recommended. Thus, Powtoon training has proven effective in improving teachers' skills, which is expected to have a positive impact on the quality of learning in elementary schools.